Craniometric assessment of gender using mastoid process - Harsha Bhayya; M L Avinash Tejasvi; B Jayalakshmi; M Mounika Reddy (Wolters Kluwer Medknow Publications, 2018)
Background: The mastoid process characteristics are of great utility in the determination of sex. Studies on human skeletal remains for sex determination have been a topic of interest among researchers. Osteometric studies using individual bones exhibiting sexual dimorphism have been reported among different populations. Skull is important in this regard as it resists adverse environmental conditions over time. The mastoid process can be used as a marker of sex determination in unidentified human skull remains. Objective: The objective of this study is to evaluate the use of mastoid process as a tool for sex determination in unidentified skeleton. Aim: The aim of this study was to evaluate the accuracy of different craniometric parameters of mastoid process in sex determination. Materials and Methods: In the present study, 50 adult human skulls of Telangana population were studied to determine the accuracy of mastoid process in sex determination. Parameters studied were length, breadth, antero-posterior diameter, size, and area of mastoid process. Results: Statistics revealed high significance (P < 0.0001) for mastoid length and size for sex determination. Conclusion: To our knowledge, this is the only study including various craniometric parameters of mastoid process.